2001
DOI: 10.1093/aje/154.5.434
|View full text |Cite
|
Sign up to set email alerts
|

Phytoestrogen Consumption and Breast Cancer Risk in a Multiethnic Population: The Bay Area Breast Cancer Study

Abstract: Research on the relation between phytoestrogens and breast cancer risk has been limited in scope. Most epidemiologic studies have involved Asian women and have examined the effects of traditional soy foods (e.g., tofu), soy protein, or urinary excretion of phytoestrogens. The present study extends this research by examining the effects of a spectrum of phytoestrogenic compounds on breast cancer risk in non-Asian US women. African-American, Latina, and White women aged 35-79 years, who were diagnosed with breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
218
7
10

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(245 citation statements)
references
References 18 publications
5
218
7
10
Order By: Relevance
“…Other risk factors, such as diet, reproductive factors, deficiency or excess of iodine, changes in height and weight, have been involved in some studies Negri et al, 1999;Dal Maso et al, 2000;Horn-Ross et al, 2001). It is not likely that any of these factors would profoundly influence the risk related to radioiodine since we found a difference between exposed and nonexposed tumours, and, for some tumours, a dose -response relationship.…”
Section: Discussionmentioning
confidence: 53%
“…Other risk factors, such as diet, reproductive factors, deficiency or excess of iodine, changes in height and weight, have been involved in some studies Negri et al, 1999;Dal Maso et al, 2000;Horn-Ross et al, 2001). It is not likely that any of these factors would profoundly influence the risk related to radioiodine since we found a difference between exposed and nonexposed tumours, and, for some tumours, a dose -response relationship.…”
Section: Discussionmentioning
confidence: 53%
“…The combined OR (summary OR ¼ 1.02, 95% CI ¼ 0.84 -1.23) from these three nested case -control studies is consistent with the finding of no association based on dietary soy isoflavones and breast cancer risk in Western populations. There were no differences in results by menopausal status (Horn-Ross et al, 2001;dos Santos Silva et al, 2004;Keinan-Boker et al, 2004;Bosetti et al, 2005;Fink et al, 2007;Verheus et al, 2007). One study examined the soy -breast cancer association by body size and reported no differences in results (Bosetti et al, 2005).…”
Section: Risk Association Studies In Low-soy-consuming Western Populamentioning
confidence: 97%
“…We estimated daily soy isoflavone intake in one study (Witte et al (1997) by assuming that one serving of tofu per week is 50 g and this is equivalent to 2.14 mg isoflavone per day. Francisco Bay Area, USA (Horn-Ross et al, 2001). Instead a considerable (25 -60%) proportion of soy isoflavones in these populations was from soy components added to typical Western foods including bakery and canned products.…”
Section: Risk Association Studies In Low-soy-consuming Western Populamentioning
confidence: 99%
See 2 more Smart Citations